Gender differences and biomechanics in the 3000m steeplechase water jump - Hunter, I.; Lindsay, B. K.; Andersen, K. R. (Journal of Sports Science & Medicine, 2008)
Since 1996, women have been competing in the 3000m steeplechase race internationally. Whenever women and men both compete in similar events with different equipment (the barriers are lower for women) consideration should be given as to how techniques should be coached differently. This study investigated the differences in water-jump technique between men and women after accounting for differences in running speed and which techniques led to maintenance of race pace through the water-jump. Eighteen men and 18 women were filmed at two major track and field meets during the 2004 season. Peak Motus 8.2 was used to digitize all seven jumps from each athlete. Various characteristics of water-jump technique were measured or calculated and compared using two multiple linear regressions (one for men and one for women) to determine which characteristics led to maintaining race pace speeds through the water jump obstacle. Repeated measures ANOVA was used to determine any differences between men and women in the measured characteristics of technique.Velocity through the jump divided by race pace was predicted very well by approach velocity and landing distance for men and women. Other characteristics of the movement were non-significant. Differences between genders were found in: approach velocity, take-off distance, landing distance, push-off angle, velocity through jump, and exit velocity. Men and women steeplechasers must focus on approach velocity and landing distance to complete the water-jump close to their race pace. Coaches need to consider many characteristics of technique that differ between men and women.